2007
DOI: 10.1002/elps.200600470
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic flow mixing in zigzag microchannels

Abstract: In this study we performed numerical and experimental investigations into the mixing of EOFs in zigzag microchannels with two different corner geometries, namely sharp corners and flat corners. In the zigzag microchannel with sharp corners, the flow travels more rapidly near the inner wall of the corner than near the outer wall as a result of the higher electric potential drop. The resulting velocity gradient induces a racetrack effect, which enhances diffusion within the fluid and hence improves the mixing pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…The experimental images were captured by an optical microscope (Model: Eclipse 50i, Nikon, Japan), filtered spectrally, and then observed using a charge-coupled device camera (CCD, model: SSC-DC50A, Sony, Japan). The mixing effectiveness within the microchannel was quantified based on the intensity of the Rhodamine B sample using the mixing index presented in Lin et al (2005) and Chen and Yang (2007), i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental images were captured by an optical microscope (Model: Eclipse 50i, Nikon, Japan), filtered spectrally, and then observed using a charge-coupled device camera (CCD, model: SSC-DC50A, Sony, Japan). The mixing effectiveness within the microchannel was quantified based on the intensity of the Rhodamine B sample using the mixing index presented in Lin et al (2005) and Chen and Yang (2007), i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A droplet-based microfluidic system was also reported to achieve fast mixing by inducing chaotic flow inside droplets moving through winding microchannels [10]. In addition, Chen and Yang [11] investigated electrokinetic mixing in zigzag microchannels with sharp and flat corner geometries, and found that the electrokinetic mixing index of the flat-corner zigzag channel is better than that of the conventional sharp-corner microchannel. Active mixers utilize external driving forces to disturb the flow and thus to enhance mixing.…”
Section: Introductionmentioning
confidence: 98%
“…This type of mixer typically relies on complex flow patterns, which define unique structures of different passive mixers. Various passive micromixers have been reported: branched-microchannels (Erbacher et al 1999), staggered herringbone mixers (Stroock et al 2002;Villermaux et al 2008), zigzag-shaped channels (Chen and Yang 2007;Egawa et al 2009), three-dimensional nanopore structures (Park et al 2009), and split-and-recombine configurations (Hardt et al 2005(Hardt et al , 2006Tofteberg et al 2010). Active mixers, on the other hand, operate with external energy input and thus mixing is achieved with various external disturbances.…”
Section: Introductionmentioning
confidence: 99%